The taming of the shrew - Shakespeare, William, 1564-1616 (Mumbai : Wilco International, 2023)
Lovely Bianca has a queue of admirers anxious to marry her. But her older sister, Katharina, must get married first. Katharina has such a fiery temper she is know as "the shrew", and no man is brave enough to propose. Can Petruchio tame her with his outrageous behaviour?
Keywords: Man-woman relationships -- Drama; Married people -- Drama